A large area TOF-tracker device based on multi-gap Resistive Plate Chambers - Assis, P. (2022)
The TOF-tracker concept, the simultaneous measurement of accurate time and bi-dimensional space coordinates in a single gaseous detector, has been previously demonstrated. The detector yielded a time resolution of 77 ps σ along with a bi-dimensional position resolution of 38 μm σ over a full active area of 60 × 60 mm2. In here, we report about a large area, 1550 × 1250 mm2, TOF-tracker device, tested by tracking cosmic muons, yielding a position resolution down to 1.33 mm σ, a simultaneous time resolution of 150 ps σ and 92% detection efficiency, over the entire area of the detector. The sub-millimetre electronic resolution of the readout chain suggests that the position resolution here reported could be dominated by non-corrected systematic effects and therefore it could be yet significantly improved.